Comparative Analysis of Gear Efficiency for Portunus sanguinolentus Fishing along the Ramanathapuram Coast of Tamil Nadu, India - Vaishnav, Anand; Lal, Jham; Chouhan, Nayan; Debbarma, Payel; Kurre, Deepika; Singh, Nongthongbam Sureshchandra; Pati, Bikas Kumar; Bhooleshwari; Kumar, Shailendra; Chakraborty, Adipta (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study, which was conducted along the Ramanathapuram coast of Tamil Nadu, India, investigated the capture composition of a three-spot swimming crab (Portunus sanguinolentus) across various fishing gear from November 2019 to October 2020. The fishermen employed bottom-set gillnets, trammel nets, and trawl nets in 29 different fishing areas within a range of 1-50 nautical miles. The fishing vessels used included wooden boats, known as 'Vallam,' equipped with inboard engines, and FRP boats with outboard engines. Bottom-set gillnets, with mesh sizes of 80–100 mm, predominantly caught crabs, whereas trammel and trawl nets were primarily used to capture fish and cephalopods, with crabs being caught as bycatch. The size distribution of the collected P. sanguinolentus ranged from 26 to 87 mm in carapace length and 61 to 189 mm in carapace width. The mean size fell between 115 and 125 mm in width and 45 to 60 mm in length. Catch per unit effort analysis revealed that bottom-set gillnets contributed 82.77% of the catch, followed by 3.69% from trammel nets and 13.53% from trawl nets.